Risk factors for cognitive dysfunction amongst patients with cardiovascular diseases - Tunde Pal; Tunde Pal; Laszlo Barna Iantovics; Zoltan Preg; Zoltan Preg; Eniko Nemes-Nagy; Eniko Nemes-Nagy; Kinga-Ilona Nyulas; Dragos-Florin Baba; Dragos-Florin Baba; Marta German-Sallo; Marta German-Sallo (Frontiers Media S.A., 2024)
BackgroundThe impact of cardiovascular diseases on cognition raises important research questions. The study aimed to investigate the relationship between demographic data, cardiovascular diseases, kidney disease and depressive symptoms on cognition.MethodsA cross-sectional study of patients with cardiovascular diseases was performed. The Montreal Cognitive Assessment (MoCA) was applied for cognitive evaluation. Based on MoCA three groups were defined: preserved cognition, mild, and advanced cognitive dysfunction (CD). Data were analyzed using Cronbach alpha (Cα) and McDonald's ω (Mω) for internal consistency. The Chi-square test, Cramer's V test, and correlation analyses were also applied.ResultsOf 628 patients, 55.2% had mild CD, and the mean age was 67.95 (SD 9.53) years. Cα and Mω were 0.7, indicating good internal consistency. We found a moderate positive correlation between depression and the severity of CD (r = 0.25, p = 0.0001). A weak association between CD and female gender (p = 0.016), atrial fibrillation (p = 0.03), stroke (p = 0.009), and a moderate association for age group (p < 0.0001), education level (p < 0.0001), smoking (p < 0.0001), and renal dysfunction (p < 0.0001) was found. Age ≥ 70 years, eGFR 30-59 mL/min/1.73m2 significantly increased the likelihood for mild and advanced CD, while smoking and > 9 classes decreased it. Female gender, history of atrial fibrillation, and stroke significantly increased the likelihood of advanced CD.ConclusionMild CD was the most common in patients with cardiovascular diseases. Older age, lower education, being a non-smoker, and renal dysfunction were risk factors for both mild and advanced CD. Female gender, previous diagnosis of atrial fibrillation, and stroke are risk factors for advanced CD.